Entrepreneurial Networking and Performance of Ugandan Manufacturing SMEs: The Mediating Role of Innovation Capabilities - Bakashaba, Rennie; Musiita, Benjamin; Nabachwa, Sarah (Journal of Economics and Behavioral Studies, 2024)
This study investigates the potential impact of innovation capacities on the relationship between entrepreneurial networking and the performance of small and medium-sized manufacturing enterprises (SMEs) in Mbarara City. The target population of the study was 248 SMEs, according to MoFPED (2022). 205 SMEs were obtained when the sample size was calculated using Krejcie and Morgan’s (1970) tables. With 186 respondents and SMEs, the response rate was 91%. Data was collected using a cross-sectional research design. To determine the mediating link, the four stages of Baron and Kenney (1986) was completed and every direct influence of the research variables had to meet a substantial requirement. The prerequisites were met and there was a significant direct association (Beta=0.673; p<.01) between entrepreneurial networking and SMEs’ performance. Furthermore, there was a direct substantial association (Beta=0.437; p<.01) between innovation capabilities and the performance of SMEs, and a significant correlation (Beta=0.166; p<.01) was found between entrepreneurial networking and innovation capabilities. The association between entrepreneurial networking and the performance of SMEs decreased from Beta=0.673 to Beta=0.617 when innovation capabilities were taken into account, although the relationship remained statistically significant. This suggests that the relationship between entrepreneurial networking and the performance of SMEs is mediated by innovative capabilities. The model’s indirect outcome is given by the percentage of 8.32%, indicating that 91.68% explains the direct effect. The study advises policymakers to encourage SMEs to innovate and promote entrepreneurial networking by organizing workshops/seminars where entrepreneurs can interact with each other and thus boost their innovativeness which will enhance SME performance.